2022
DOI: 10.3390/foods11162537
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Tea Polyphenols, Free Amino Acids and Caffeine Content in Tea Leaves during Wilting and Fermentation Using Hyperspectral Imaging

Abstract: The withering and fermentation degrees are the key parameters to measure the processing technology of black tea. The traditional methods to judge the degree of withering and fermentation are time-consuming and inefficient. Here, a monitoring model of the biochemical components of tea leaves based on hyperspectral imaging technology was established to quantitatively judge the withering and fermentation degrees of fresh tea leaves. Hyperspectral imaging technology was used to obtain the spectral data during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…Despite the expectation that HC, LDA, KNN, Log-Reg, Nai-Bay, RF, SGD, SVM, and Tree [ 12 , 31 ] would have the highest precision and accuracy, our study found otherwise. Instead, SVM, PLS, and RF algorithms showed the highest accuracy for lettuce pigment phenotyping when used with a regression model [ 20 , 36 ].…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Despite the expectation that HC, LDA, KNN, Log-Reg, Nai-Bay, RF, SGD, SVM, and Tree [ 12 , 31 ] would have the highest precision and accuracy, our study found otherwise. Instead, SVM, PLS, and RF algorithms showed the highest accuracy for lettuce pigment phenotyping when used with a regression model [ 20 , 36 ].…”
Section: Discussioncontrasting
confidence: 93%
“…Our study proposed that simple methods combined with AIAs (AdB, CN2, G-Boo, and NN algorithms) can classify lettuce varieties with high accuracy and precision based on results from at least eleven lettuce plants [ 1 ]. Therefore, algorithms such as iPLSR, PLSR, LDA, RF, SGD, and SVR over VIs were used to predict and classify optical leaf properties with high precision [ 12 , 29 ]. Some research reports successful prediction of pigments by VIs, with models developed by the best-performing RF, KNN, SGD, and Tree algorithms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the traditional picking method, Wuyi rock tea is mainly picked with one bud and three leaves. During the withering process, fresh tea leaves begin to lose a lot of water and soften, and substances in the leaves begin to transform and accumulate, laying the foundation for subsequent processing (Mao et al., 2022). Shaking and tumbling makes the edges of the leaves of the tea trees begin to break, and the leaves are affected by external stresses (Zeng et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, HSI system (GaiaField-Pro, Jiangsu Dualix Spectral Image Technology Co. Ltd) was used to collect spectral information of tea leaves in the range of 397-1008 nm. The composition, specifications and parameters of the HSI system were the same as those in reference ( Mao et al., 2022 ). The spatial resolution of hyperspectral images collected in this study was 960 × 1101 (Space × Spectrum), the spectral resolution was 3.5 nm and the number of spectral channels was 176.…”
Section: Methodsmentioning
confidence: 99%